ON THE ROAD TO FAILURE? THE POLITICAL ECONOMY OF THE BRAZILIAN CRISIS (Desarrollo Económico. Revista de Ciencias Sociales, 2022)
The objective of this article is to think theoretically about the difficult combination between political democracy and socio-economic development in the conditions of contemporary capitalism. This exercise will be carried out through the analysis of the recent Brazilian case, more specifically through a reflection on the crisis that has hit the country in the recent years, leading to the dismissal of re-elected president Dilma Rousseff and the destruction of the government coalition created by her predecessor, Luiz Inácio Lula da Silva. Through an analysis malgamating both a path dependent view of the domestic political economy, and the institutional instances of interlocution between State and civil society (including the business actors), we investigate the hypothesis that the economic slowdown provoked a shift in the correlation of congressional and societal forces, hindering the social democratic platform in Brazil after the elections of 2014. For such intellectual effort, we resorted to the temporal frame comprising between 1994 and 2017, in order to account for the most substantive changes in the agenda that occurred during the period of the Pt government vis-à-vis the Brazilian Social-Democracy Party and the subsequent president, Michel Temer.
Keywords: Brasil, Economic crisis, Political crisis, Critical juncture